2007
DOI: 10.1038/mt.sj.6300155
|View full text |Cite
|
Sign up to set email alerts
|

Bystander Killing of Malignant Glioma by Bone Marrow–derived Tumor-Infiltrating Progenitor Cells Expressing a Suicide Gene

Abstract: Adult stem cells are promising cellular vehicles for therapy of malignant gliomas as they have the ability to migrate into these tumors and even track infiltrating tumor cells. However, their clinical use is limited by a low passaging capacity that impedes large-scale production. In the present study, a bone marrow-derived, highly proliferative subpopulation of mesenchymal stem cells (MSCs)-here termed bone marrow-derived tumor-infiltrating cells (BM-TICs)-was genetically modified for the treatment of malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 38 publications
3
64
0
3
Order By: Relevance
“…Because the bladder is an anatomically accessible organ, the therapeutic adenovirus can come in direct contact with the bladder cancer through intravesicular administration. Furthermore, approximately 80% of newly diagnosed bladder cancer patients have non-muscle-invasive bladder cancer (NMIBC) or carcinoma in situ (CIS) [26], so bladder instillation may be clinically effective for RGDAd-UPII-TK and GCV delivery, and the bystander killing effect of phosphorylated GCV can expand the apoptosis of the remaining uninfected bladder cancer cells [18]. Another problem is that the efficacy was poor when the therapeutic adenoviruses were used as standalone therapies, but suitable efficacy was obtained when used in combination with conventional therapies such as chemotherapy and radiotherapy [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the bladder is an anatomically accessible organ, the therapeutic adenovirus can come in direct contact with the bladder cancer through intravesicular administration. Furthermore, approximately 80% of newly diagnosed bladder cancer patients have non-muscle-invasive bladder cancer (NMIBC) or carcinoma in situ (CIS) [26], so bladder instillation may be clinically effective for RGDAd-UPII-TK and GCV delivery, and the bystander killing effect of phosphorylated GCV can expand the apoptosis of the remaining uninfected bladder cancer cells [18]. Another problem is that the efficacy was poor when the therapeutic adenoviruses were used as standalone therapies, but suitable efficacy was obtained when used in combination with conventional therapies such as chemotherapy and radiotherapy [27].…”
Section: Discussionmentioning
confidence: 99%
“…HSV-TK can convert ganciclovir (GCV) into GCV-monophosphate (GCV-MP), which will be recognized by cellular kinases and then converted into GCV-triphosphate (GCV-TP), which is a guanine nucleoside analogue that may cause DNA chain termination and subsequent apoptosis cell death. Additionally, GCV-MP can passively diffuse into neighboring cells to exert a “bystander effect”, which can expand the elimination of tumor cells [1821]. …”
Section: Introductionmentioning
confidence: 99%
“…BM-hMSCs demonstrate significant promise as cell-based delivery vehicles for anti-glioma therapeutics 13, 15-17, 19, 43, 44 . However, evidence suggests that in GSCXs, the ‘gold standard’ of glioma models, these cells do not home or extravasate equally 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Miletic and colleagues found that MSCs engineered to express herpes simplex virus thymidine kinase (HSV-TK) and injected into the tumor or the vicinity of the tumor, infiltrated solid parts as well as the border of glioma models in rats, and ultimately showed high therapeutic efficacy by significant reduction of tumor volumes through bystander-mediated glioma cell killing (Miletic et al, 2007). In 2012, Choi et al studied human adipose tissue (hAT)-derived MSCs and prodrug gene therapy against brainstem gliomas in rat models.…”
Section: Stem Cell -Prodrug Therapymentioning
confidence: 99%